Implementation Fidelity and the Design of a Fractions Intervention. (November 2019) - Crawford, Lindy; Freeman, Barbara; Huscroft-D'Angelo, Jacqueline; Quebec Fuentes, Sarah; Higgins, Kristina N.
Interventions are implemented with greater fidelity when their core intent is made explicit. The core intent of this intervention was to increase access to higher order learning opportunities for students with learning disabilities or difficulties in mathematics through use of research and practice from the fields of special education and mathematics education. Four steps undertaken in the development of a Tier II fraction-based mathematics intervention designed to improve the conceptual understanding of students with learning disabilities or difficulties are described in this article: (a) articulation of a logic model, (b) delineation of intervention components, (c) analysis of reliability data related to implementation fidelity, and (d) pilot testing to measure implementation fidelity and student outcomes. Results of the pilot study demonstrated no significant effect for the component of technology; however, significant pre–post differences were found in the performance of all groups on their conceptual understanding of fractions as numbers.